Educational competences and emotional intelligence level of teachers - Romanowska-Tolloczko, Anna (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose : Determination of the relationship between the level of emotional intelligence and educational competences of teachers. Material and methods: The study was conducted among 120 primary school teachers. Assessment of the competence of teachers were analysed by means of a questionnaire constructed by the author of the elaboration, and the study of emotional predispositions used Two-dimensional Emotional Intelligence Inventory DINEMO. Results: It was found that teachers have a much lower level of educational competences in comparison to the substantive and methodical competences. Sphere of educational competences is the area in the work of teachers, which causes the most problems, and to which they feel the least prepared. The results of research on emotional intelligence showed variation in the levels of teachers predispositions Most of them - 54% is characterized by the average level of the selected features, 30% achieved high results, and 16% have low level of understanding and recognition of emotions. Conclusions: It was found that there is a correlation between the level of emotional intelligence and ability to cope in the educational situations. Understanding one’s own and other people’s emotions favors achieving high educational competences.